Food security in an uncertain world an international perspective - Schmitz, Andrew; Kennedy, P. Lynn.; Schmitz, Troy Gordon (Bingley, U.K. : Emerald, 2015)
International trade agreements are central to food security. The links between trade and the four dimensions in food security (availability, access, utilization, and stability) are examined. Freer trade in agricultural products provides additional food security. This is bolstered by factors such as increasing the use of GMOs, reducing food waste, and increasing investment in research and development. Also important is the ability of poor people to obtain food in the presence of transportation bottlenecks. Since low-income households spend most of their money on food, policy makers need to be aware of the harm caused by high and volatile food prices. Thus, food security and poverty are very much linked. We provide an understanding of the meaning and measurement of food security and the impacts of government policies in poverty alleviation. In terms of investment in research and development, even with increased productivity, problems attached to food security will remain unless there are significant changes in global income distribution. Global food shortages are due more to the lack of purchasing power rather than lack of food supplies, with the food gap continuing to widen.
Food security : starvation in the midst of plenty / Andrew Schmitz, P. Lynn Kennedy -- Trade and food security : links, processes, and prospects / Ekaterina Krivonos, Jamie Morrison, Eleonora Canigiani -- Macroeconomic policies and food security / Eugenio Di<U+0301>az-Bonilla -- Food security measurement : an empirical approach / David Magan<U+0303>a-Lemus, Jorge Lara-A<U+0301>lvarez -- Food security issues : concepts and the role of emerging markets / Shida Rastegari Henneberry, Claudia Diaz Carrasco -- An income-based food security indicator for agricultural technology impact assessment / John Antle, Roshan Adhikari, Stephanie Price -- Dual nature and the human face of food (in)security / Dragan Miljkovic -- Innovations in international food assistance strategies and therapeutic food supply chains / Lisa F. Clark, Jill E. Hobbs -- Managing high and volatile food prices in developing countries since 2000 / Maros Ivanic, Will Martin -- Food security and anti-piracy strategies : the economics of protecting world food program shipments / William A. Kerr -- World population, food growth, and food security challenges / William H. Meyers, Nicholas Kalaitzandonakes -- Genetic engineering and food security : a welfare economics perspective / Prithviraj Lakkakula, Dwayne J. Haynes, Troy G. Schmitz -- Who will feed the growing population in the developing nations? Implications of bioenergy production / Won W. Koo, Richard Taylor -- Food security and conflict / Donna Mitchell ... [et al.] -- Major trends in diets and nutrition : a global perspective to 2050 / Siwa Msangi, Miroslav Batka -- Dietary change and global drivers of change : how can we improve the nutritional status of the bottom billion? / Siwa Msangi, Miroslav Batka -- Regional and national rice development strategies for food security in West Africa / Eric J. Wailes, Alvaro Durand-Morat, Mandiaye Diagne.
Print version record
Keywords: Business & Economics -- Development -- Economic Development; Business & Economics -- Development -- Sustainable Development; Development economics; Food supply; Food conservation; Food consumption